A cellular view of Nf2 in liver homeostasis and tumorigenesis - Breuhahn, Kai; Schirmacher, Peter (Developmental cell, 2010)
How liver adjusts and stabilizes its size is unsolved so far; the answers to this question may also provide insights into mechanisms of hepatocarcinogenesis. Two recent papers suggest a role for Merlin/Nf2 in control of liver cell turnover, but results appear conflicting at first glance.
Gesehen am 01.03.2023